Effect of flaxseed oil on colostrum composition, immunoglobulin concentration and immune response in neonatal friesian calves - Abuelhamd, Mohamed; El-Diahy, Yasser; El-Maghraby, Mahmoud; Elshora, Mohamed; Algaml , Nabeel; Badr, Anas (Journal of the Hellenic Veterinary Medical Society, 2024)
The current study aimed was to investigate how flaxseed oil supplementation affects colostrum’s composition, immunoglobulin concentration, and immunological response of newborn calves. A total of 28 Friesian cows during the late pregnant (pregnant 8 months) were divided into two similar groups (14 cows in each group). The first group (G1) consider as a control group, and the second group (G2) was supplemented with 2.5% DMI flaxseed oil for 4-6 weeks before calving. Results showed that the days had lower significantly in immunoglobulin concentrations of colostrum, IgG, IgA, IgM and total Ig, while the highest concentration value were on the first day and lowest values were on the third day of age on all calves. In addition, colostrum composition in cows (G2) was significantly higher in protein, fat and total solids values compared with cows in G1. Immunoglobulin concentrations of colostrum in cows G2 were significantly higher in IgG, IgA, and total Ig compared with the control (G1). Besides that, the higher significant values of IgG, IgA, IgM and total Ig were on the seventh day, while the lowest values were on the first day in newborn calves. Overall means concentrations of immunoglobulin IgG, IgM and Ig in blood plasma were higher significantly in newborn calves which received flaxseed oil (G1) compared with calves in G2.